Individualised placement support as an employment intervention for individuals with chronic pain: a qualitative exploration of stakeholder views. Issue 3 (August 2020) - Holmes, Michelle M; Stanescu, Sabina C; Linaker, Catherine; Price, Catherine; Maguire, Nick; Fraser, Simon; Walker-Bone, Karen
No abstract available